Synergy - Sankaran, Rajan (Homœopathic Links, 2012)
The author discusses that the Sensation approach should be used as an interdependent and flexible tool. By triangulating between three angles from which a case can be approached and understood – genius, symptoms, and system – a powerful synergy is established with accurate prescriptions as a result.
Keywords: Case taking; Case analysis; Synergy; Symptoms; System; Genius; Sensation